Secret knowledge : rediscovering the lost techniques of the old masters - Hockney, David (New York : Viking Studio, 2001)
David Hockney makes a visual presentation of his theory that many Western artists of the past, dating from the early fifteenth century, used mirrors and lenses to create living projections which were then used to produce drawings and paintings. Includes a collection of extracts from documents used in Hockney's research, as well as related notes, essays, and letters.
Includes bibliographical references (p. 287-289) and index.
Adult
Keywords: Camera lucidas; Camera obscuras; Drawing -- Technique -- History; Optics and art; Painting -- Technique -- History; Painting -- Technological innovations -- History; Art; Drawing -- Technique -- History; Optical data processing; Optical instruments; Painting -- History; Painting -- Technique -- History